1995
DOI: 10.1128/jb.177.19.5582-5589.1995
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and regulation of a new putative cell wall hydrolase gene, cwlD, which affects germination in Bacillus subtilis.

Abstract: DNA sequencing of a region upstream of the mms223 gene of Bacillus subtilis showed the presence of two open reading frames, orf1 and orf2, which may encode 18-and 27-kDa polypeptides, respectively. The predicted amino acid sequence of the latter shows high similarity to a major autolysin of B. subtilis, CwlB, with 35% identity over 191 residues, as well as to other autolysins (CwlC, CwlM, and AmiB). The gene was tentatively named cwlD. Bright spores produced by a B. subtilis mutant with an insertionally inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
125
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 47 publications
10
125
1
Order By: Relevance
“…The mutation of sleB was more effective in NAFM5 than in 168. Sekiguchi et al (1995) reported that the germination rate of the cwlD mutant in B. subtilis was less than 3.7 x 10 -8 , but our results were 1.9x 10 -4 and 1.7 x 10 -3 for 168 and NAFM5, respectively. Popham et al (1996) showed that the germination rate of the cwlD mutant in B. subtilis was 5 x 10 -4 (with the respect to the wild type).…”
Section: Analysis Of Nattocontrasting
confidence: 83%
See 4 more Smart Citations
“…The mutation of sleB was more effective in NAFM5 than in 168. Sekiguchi et al (1995) reported that the germination rate of the cwlD mutant in B. subtilis was less than 3.7 x 10 -8 , but our results were 1.9x 10 -4 and 1.7 x 10 -3 for 168 and NAFM5, respectively. Popham et al (1996) showed that the germination rate of the cwlD mutant in B. subtilis was 5 x 10 -4 (with the respect to the wild type).…”
Section: Analysis Of Nattocontrasting
confidence: 83%
“…These results suggest that an early germination event (i.e., dipicolinic acid release) was not affected by the double mutations in either strain. These data were supported by the results for each single mutation in B. subtilis (Sekiguchi et al 1995;Moriyama et al 1996). Phase-contrast microscopy of the wild type and mutants is shown in Fig.…”
Section: Analysis Of Spore Germinationsupporting
confidence: 72%
See 3 more Smart Citations